Нове Законодавство України про Національну поліцію і поліцейську діяльність. Яким йому бути? - Біленчук, П.; Bilenchuk, P.; Ярмолюк, А.; Iarmoliuk, A. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
В статті системно розкривається історіографія створення кодексів як в Україні, так і в інших країнах світу, а також наголошується на тому, що реформа системи органів правопорядку в Україні повинна отримати ефективне законодавче оформлення не в звичайному законі, а в Поліцейському кодексі України. Концептуальні засади реформування системи правоохоронних органів повинні виходити з того, що співробітники поліції є безпосереднім обличчям держави; необхідно прагнути закласти в законодавство такі світоглядні правові підвалини, які б сприяли формуванню високого рівня довіри громадян до поліції. Також потрібно зробити процес проходження служби поліцейського та його кар’єрного зростання прозорим і об’єктивним. The article deals with the historiography of establishing Codes both in Ukraine and other countries of the world which is revealed systematically in the article. The author lays emphasis on the necessity to create Police сode of Ukraine that could provide effective legislative support for the law enforcement authorities in the course of reforming the existing system. Conceptual principle of the system reforming process implies security guarantees to the citizens, society, state, security against threats, challenges and dangers. The basic idea of the reform is to make the police staff a decent face of the state. The author suggests that radical legislative reformation changes of the police forces imply radical modification of the legal foundations of the laws which would facilitate formation of the public confidence in the police like in Georgia, Canada, Norway, Germany, the USA, Finland, Japan and other countries of the world. It is necessary to make career development of the policemen transparent and objective on the basis of just evaluation of the results of their work and thus guarantee them perspectives to be promoted owing to personal qualities and professional achievements.
New Legislation of Ukraine on the National Police and Police Activities. What Should It Be?
Keywords: реформування; Національна поліція України; Поліцейський кодекс України; довіра громадян до поліції; National police of Ukraine; Police сode of Ukraine; public confidence in the police